1989
DOI: 10.1177/140349488901700209
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Effect on Mother-Infant Behaviour of Extra Contact During the First Hour Post Partum. V. Follow-up at Three Years

Abstract: Primiparous mothers and their infants who had had an extra 15-20 minutes skin-to-skin and suckling contact (P+) during the first hour after delivery behaved differently, had a longer duration of breast-feeding, and expressed different opinions on child rearing practices at follow-ups 36 hours, 3 and 12 months after delivery as compared with a control group (P) of primiparous mothers and their infants, who were given routine care immediately after birth. The present report is based on parts of the results of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0
1

Year Published

1994
1994
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 14 publications
2
16
0
1
Order By: Relevance
“…Barr et al [1989] reported that breast-fed infants have a more difficult temperament than those who were formulafed and, therefore, attracted significantly more time and attention than those children. A study done by Wiberg et al [1989] showed that mothers who had had closer contact with their infants presented a higher prevalence and a longer duration of breast-feeding. We suspect this closer contact may foster the transmission of oral biota from mothers to their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Barr et al [1989] reported that breast-fed infants have a more difficult temperament than those who were formulafed and, therefore, attracted significantly more time and attention than those children. A study done by Wiberg et al [1989] showed that mothers who had had closer contact with their infants presented a higher prevalence and a longer duration of breast-feeding. We suspect this closer contact may foster the transmission of oral biota from mothers to their infants.…”
Section: Discussionmentioning
confidence: 99%
“…Healthy infants should be placed and remain in direct skin-to-skin contact with their mothers immediately after delivery until the first feeding is accomplished. [156][157][158] • The alert, healthy newborn infant is capable of latching on to a breast without specific assistance within the first hour after birth. 156 Dry the infant, assign Apgar scores, and perform the initial physical assessment while the infant ‡ There is a difference of opinion among AAP experts on this matter.…”
Section: Recommendations On Breastfeeding For Healthy Term Infantsmentioning
confidence: 99%
“…To collect data about these aspects is the main interest of the present study. Existing empirical evidences show that maternal attachment during pregnancy (for example, Fuller, 1990;Kemp et al, 1990) or immediately after delivery (for example, Cernadas et al, 2003) is associated with the quality of the mother-to-infant interaction and care (namely breastfeeding), which interfere in the child development (for example, Wiberg et al, 1989). Few are the studies that focus on the parent's emotional involvement with the newborn, and almost all are about mothers, so practically no information exists about fathers (Robson & Mandel, 1985).…”
Section: Parent-infant Initial Emotional Involvement 523mentioning
confidence: 99%